Knowledge and Attitudes Among Medical Students Toward the Clinical Usage of e-Cigarettes: A Cross-Sectional Study in a University Hospital in Saudi Arabia - Alzahrani,Sami; Alghamdi,Rawan A; Almutairi,Ahmed Mabruk; Alghamdi,Ali Ahmed; Aljuhani,Abdullah Abdulwahab; ALbalawi,Abdulrahman Hamed (Risk Management and Healthcare Policy, 2021)
Sami H Alzahrani,1 Rawan A Alghamdi,2 Ahmed Mabruk Almutairi,3 Ali Ahmed Alghamdi,3 Abdullah Abdulwahab Aljuhani,3 Abdulrahman Hamed ALbalawi3 1Family Medicine Department, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 2Ibn Sina National College for Medical Studies, Jeddah, Saudi Arabia; 3Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Sami H AlzahraniFamily Medicine Department, Faculty of Medicine, King Abdulaziz University, PO Box 80205, Jeddah, 21589, Saudi ArabiaTel +966 9500004062Email drsamihz@gmail.comBackground: To assess knowledge and attitudes about e-smoking among undergraduate medical students, specifically focused on favorable view of therapeutic e-cigarette use for smoking cessation or harm reduction.Methods: This cross-sectional study included medical students at King Abdulaziz University, Saudi Arabia. A six-item subscale was used to explore knowledge and attitudes about the therapeutic use of e-cigarettes, measuring participants’ likelihood of favoring such use. A four-item questionnaire measured confidence and importance of being educated about smoking and e-smoking, in addition to sources of knowledge about e-cigarettes.Results: A total of 399 students participated. Smoking history included current smokers (19.8%) and ex-smokers (6.5%), while e-cigarettes were tried by 36.6% and are currently used by 11.5%. A minority (13.5%) believed that e-cigarettes are FDA-approved for smoking cessation, while approximately one-third believed e-smoking lowers cancer risks (31.1%) and could help with smoking cessation (31.1%). Further, 35.9% agreed or strongly agreed that e-cigarettes are better for patients than tobacco products, and 17.5% were likely to recommend e-smoking to their patients for smoking cessation. Reliability of the six-item scale showed Cronbach’s alpha = 0.676, which was enhanced to 0.746 after deletion of one item about addictiveness. Using the corrected five-item scale, 23.6% of the participants would favor therapeutic use of ...